Clinically amyopathic dermatomyositis with interstitial lung disease double-positive for anti-MDA5 and anti-PL12 antibodies. (2022) - Hiramatsu, Toshiya; Murano, Moeko; Nakai, Shogo; Murakami, Yurina; Nishimoto, Koji; Matsushima, Sayomi; Harada, Masanori; Uto, Tomohiro; Sato, Jun; Imokawa, Shiro; Suda, Takafumi
Abstract: Anti-melanoma differentiation-associated gene 5 (MDA5) and anti-aminoacyl-tRNA synthetase (ARS) antibodies are two major myositis-specific autoantibodies with distinct clinical features. However, the clinical course remains unclear in patients with clinically amyopathic dermatomyositis (CADM)-interstitial lung disease (ILD) who have co-existing anti-MDA5 and anti-ARS antibodies. Here, we describe the case of a 32-year-old woman with CADM-ILD who had anti-MDA5 and anti-PL12 antibodies. Her serum ferritin level was within the normal range. However, chest computed tomography revealed bilateral lower-lobe consolidation and ground-glass opacities. Treatment with prednisolone and immunosuppressants was successful in improving the skin lesion and ILD, but relapse occurred on reducing the dose of prednisolone. These clinical features match those of anti-ARS antibody-positive dermatomyositis-ILD. Because these two conditions show significantly different clinical features and require different intensities of treatment, clinicians should carefully follow-up these patients throughout the course of the disease.